IMPLEMENTASI TRADISI GREDOAN PADA MASYARAKAT USING SEBAGAI SPOT TOURISM DI DESA MACANPUTIH - Aulia Rahmat Mashuri; Subur Bahri; Hary Priyanto (JURNAL KATARSIS, 2021)
Abstract: The Implementation Of Gredoan Tradition at Using Tribe as Tourism Spot in Macan Putih Village, Kabat Sub-District, Banyuwangi; A Study on Regional Regulation Number 1/2007 about Tourism Village). Gredoan tradition as tourism spot is a tradition which is done by Macanputih Village society. It is an honor act toward the culture that they have and as the event of looking for a life partner. Besides that, it is also held as the celebration of Prophet Muhammad SAW Maulid and to attract tourist. The purpose of this study were to find out and describe the role of Macanputih Village government and the participation of its society at the event of gredoan tradition. This research was descriptive qualitative research and the data collection was conducted through observation, interview, and documentation. The implementation of Edward III policy was the theory that was used in this research. Furthermore, the result of the study showed that there were four aspects which could be represented. First, the Communication Aspect was the communication which was done among Department of Tourism and Culture of Banyuwangi government, Kabat sub-district and the local government of Macanputih Village with the society was good. Second, the resources such as human resources, information, authority, funds and also the supporting facilities which were used in the implementation of gredoan was sufficient enough. Then, the dispositions aspect that had been done by the local government was well-defined. The last, bureaucratic structure. In the implementation of the bureaucratic structure was appropriate with the SOP that was determined by government. In addition, the coordination of Fragmentation principal had been associated well.